Identification of a putative man-made object from an underwater crash site using CAD model superimposition. (April 2018) - Vincelli, Jay; Calakli, Fatih; Stone, Michael; Forrester, Graham; Mellon, Timothy; Jarrell, John
Highlights: A purported Lockheed Electra 10E window slide rail was identified in wreckage video. A high degree of fit was measured when the object was compared to a 3D model. A survey of the adjacent area did not identify a natural origin of the object. Abstract: In order to identify an object in video, a comparison with an exemplar object is typically needed. In this paper, we discuss the methodology used to identify an object detected in underwater video that was recorded during an investigation into Amelia Earhart's purported crash site. A computer aided design (CAD) model of the suspected aircraft component was created based on measurements made from orthogonally rectified images of a reference aircraft, and validated against historical photographs of the subject aircraft prior to the crash. The CAD model was then superimposed on the underwater video, and specific features on the object were geometrically compared between the CAD model and the video. This geometrical comparison was used to assess the goodness of fit between the purported object and the object identified in the underwater video.